PENGARUH STRATEGI PEMBELAJARAN KOOPERATIF THINK PAIR SHARE DAN MINAT BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SEKOLAH DASAR NEGERI 104192 TANDEM HILIR II DELI SERDANG - Sufairi Sufairi (Universitas Islam Negeri Sumatera Utara Medan, 2019)
The purpose of this study was to find out: (1) learning outcomes of IslamicReligious students taught with cooperative learning strategies think pairshare and expository learning strategies, (2) student learning interest afterusing the think pair share learning strategy, and (3) the influence ofstrategy learning and interest in learning about the learning outcomes ofIslamic Education. The research was conducted at 104192 PublicElementary School Tandem Hilir II Deli Serdang. This type of research isquasi-experimental. The study population was all class V students spreadin 3 classes. The sampling technique used is cluster random sampling. Theinstruments of data collection are questionnaires and tests. The dataanalysis technique used is the analysis of two-lane variants on the test α =0.05. The results showed: (1) the average learning outcomes of IslamicReligious Education students taught with TPS learning strategies ( X =29.32) higher than the average learning outcomes of Islamic ReligiousEducation students taught with expository learning strategies ( X = 27)with Fcount = 13.32 > Ftable = 4.00, (2) the average learning outcomes ofIslamic Education students with high learning interest ( X = 29.90) higherthan the learning outcomes of Islamic Education students with lowlearning interest ( X = 26.20), with Fcount = 10.41 > Ftable = 4.00, and (3) thereis an interaction between learning strategies and interest in learning withFcount = 12.51 > Ftable = 4.00.